A community health promotion project: Amazing Race for Heart Health - Reese, Jessica A.; Guy, Carla; Jay, Halana; Ali, Tauqeer; Lee, Elisa T.; Zhang, Ying (Frontiers in Epidemiology, 2023)
Introduction: American Indians have higher rates of cardiovascular disease (CVD), likely due to disproportionate burden of diabetes and limited access to widespread CVD prevention programs such as Honoring the Gift of Heart Health (HGHH), a 10-week CVD risk factor awareness curriculum. Due to its length, HGHH may be difficult to complete; therefore, we aimed to evaluate a shortened CVD risk factor awareness program based on the HGHH educational materials for American Indians residing in southwest Oklahoma, entitled "The Amazing Race for Heart Health."We conducted an interventional study where each participant served as their own control (n=61), with pre-and post-intervention measurements. We included American Indians from seven tribal nations in southwest Oklahoma. At two interventional meetings we used educational materials and activities from HGHH focusing on nutrition, cholesterol, diabetes, hypertension, physical activity, and heart attack warning signs. McNemar's test was used to determine the effectiveness of the intervention on raising CVD risk factor awareness.Results: When comparing the pre-and post-survey responses, the percentage of correct responses either stayed the same or increased. Knowledge improved in 11/25 (44%, p<0.05) domains including the difference between good and bad cholesterol and types of physical activity that can prevent CVD. When considering diabetes, knowledge increased regarding the interaction between diabetes and cholesterol in the association with CVD.Discussion: These results demonstrate that the "Amazing Race for Heart Health," a shortened CVD risk factor educational program based on the HGHH educational materials, was effective at increasing awareness regarding CVD risk factors.